Competitiveness of Sharia Tourism Destination - Prajawati, Maretha Ika (MEC-J (Management and Economics Journal), 2020)
This study emphasizes that one concrete step in effort to develop sharia tourism is to pay attention to actual factors affecting the purpose of traveling in sharia tourism destinations in Malang. The study results showed that between motivation, cognitive goals, and service quality showed a relationship. Therefore, students would naturally intend to visit sharia tourism destinations. When tourism is needed by students in accordance with purpose of doing sharia tourism, then fulfilling this need will lead a tourist to bring up his attitude of loyalty to sharia tourism. Customer loyalty is very important for companies to maintain continuity of their business and activities. There is a fulfillment of tourists need if it is associated with sharia tourism destinations. This will increase the intention to visit sharia tourism destinations.Â